Educação e Educação Física escolar: em questão, o Funk - Forni, Elaine Patricia Duarte [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
A Educação Física escolar, por intermédio de seu patrimônio denominado de cultura corporal de movimento, busca trazer, para o espaço do saber, uma gama de conhecimentos educacionais, uma vez que se insere em muitas instâncias da vida dos jovens. Nesta pesquisa, o objetivo geral referiu-se à análise do funk na Educação e na Educação Física escolar sob a ótica da literatura acadêmica e de evidências orais de um grupo social representativo de estudantes, professores, pesquisadores e profissionais da educação básica, com fins de ressignificação didática de ensino-aprendizagem. Trata-se de uma pesquisa de cunho qualitativo, realizada por meio de pesquisa bibliográfica e estudo de caso. Inicialmente, fez-se a revisão de literatura para abordar a trajetória da dança, seus principais teóricos, assim como a origem e trajetória do funk no mundo e no Brasil. O universo da pesquisa deu-se em uma instituição educacional de Ensino Fundamental I e II, localizada em um município no interior do estado de São Paulo. Os instrumentos de coleta de dados foram análise de documentos, roteiro de entrevista semiestruturada com perguntas abertas para obter informação real e relevante à investigação. Para a análise e discussão, o método adotado foi a análise de conteúdo. Constatou-se: a) significados e sentidos do funk sob a ótica estudantil: as letras suscitam formas de identidade, enquanto a batida vincula os sentidos às sensações corporais e estimula os estudantes a se movimentarem; b) as práticas pedagógicas do funk na escola: tensões, limites e possibilidades: utilizar os elementos do funk modifica a relação com crianças e jovens, e transforma os modos de fazer a educação escolar; c) a cultura funk na escola: efeitos diante dos cenários preconceituosos: debater as questões culturais que envolvem o funk ajuda a repensar a sociedade brasileira como um todo, com seus fundamentos desiguais, descomedidos e racistas. Concluiu-se que, apesar da cultura funk ser reconhecida legalmente, enfrenta preconceitos de raça e classe que precisam ser discutidos na escola pública. Para isso, é necessário investir na formação contínua dos profissionais da Educação, para que desenvolvam outras maneiras de pensar a cultura dessa população e, assim, enfrentem e compreendam os preconceitos silenciados nas relações de ensino-aprendizagem em aulas da Educação Física e na educação escolar.

School Physical Education, throught its patrimony named body movement culture, seeks to bring to the space of knowledge, a series of educational skills, as it is inserted into many instances of childrens’ lives. The main objective of this research was to analyze funk in Education and in School Physical Education under the optic of academic interpretation and of oral evidence of a social group which represents students, teachers, researchers, and basic education professionals, aiming to didatically resignify the teaching-learning process. It is a research of qualitative approach, performed through bibliographical research and case study. Initially, we revised the literature to discuss the origin of the dance, its main theorists, as well as the origin and trajectory of funk in the world and in Brazil. The universe of the analysis and discussion, the method adopted was content analysis. The following results were found: a) meanings and senses of funk from the student perspective: the lyrics evoke forms of identity, while the beat links the senses to bodily sensations and encourages students to move; b) pedagogical practices of funk in schools: tensions, limits and possibilities: using funk elements changes the relationship with children and young people, and transforms the ways of providing school education; c) funk culture in schools: effects in the face of prejudiced scenarios: discussing the cultural issues surrounding funk helps to rethink Brazilian society as a whole, with its unequal, excessive and racist foundations. The conclusion was that, despite funk culture being legally recognized, it faces racial and class prejudices that need to be discussed in public schools. To achieve this, it is necessary to invest in the ongoing training of education professionals, so that they can develop other ways of thinking about the culture of this population, in addition to confronting and understanding the research took place at an educational institution of Elementary education I and II, located in a town in the interior of the state of São Paulo. The instruments for data collection were document analysis, the scripts of semi structured interviews with open questions to obtain real and relevant information for the investigation. For the analysis and discussion, the method adopted was content analysis. The following results were found: a) meanings and senses of funk from the student perspective: the lyrics evoke forms of identity, while the beat links the senses to bodily sensations and encourages students to move; b) pedagogical practices of funk in schools: tensions, limits and possibilities: using funk elements changes the relationship with children and young people, and transforms the ways of providing school education; c) funk culture in schools: effects in the face of prejudiced scenarios: discussing the cultural issues surrounding funk helps to rethink Brazilian society as a whole, with its unequal, excessive and racist foundations. The conclusion was that, despite funk culture being legally recognized, it faces racial and class prejudices that need to be discussed in public schools. To achieve this, it is necessary to invest in the ongoing training of education professionals, so that they can develop other ways of thinking about the culture of this population, in addition to confronting and understanding the prejudices that are silenced in teaching-learning relationships in Physical Education classes and in school education.
Education and School Physical Education: In question, Funk
Keywords: Cultura funk; Educação básica; Educação Física escolar; Ensino e aprendizagem; Sequência pedagógica; Funk culture; Basic education; School Physical Education; Teaching and learning; Pedagogical sequence